1996
DOI: 10.1021/la950735v
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Aspects of Protein Adsorption onto Titanium Surfaces:  Mechanism of Desorption into Buffer and Release in the Presence of Proteins in the Bulk

Abstract: The release process for adsorbed IgG molecules on titanium particle surfaces in the presence of pure buffer or IgG molecules in solution was investigated by means of radiolabeling techniques. This study is part of a general investigation of the basic mechanisms underlying exchange processes of adsorbed proteins by macromolecules in the bulk and in particular of the kinetic laws describing such processes. This study shows the existence, in the investigated time scale (from 1 to 43 h), of two different populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
10
44
0
Order By: Relevance
“…On the other hand for IgM desorption from bare silica is 0.004 ± 0.0025 min -1 and 0.00035 ± 0.00007 min -1 for monomers and dimers respectively. These values are well within the wide range of desorption rate constants (≈10 -4 min -1 to ≈1 min -1 ) found in the literature [120,[144][145][146]. Clearly, there are two important inferences: the monomer desorbs faster than the dimer for both surfaces, and the propensity for both the monomers and dimers of IgM to stay adsorbed on the gelatin-passivated surface is lower.…”
Section: N Desg Mt(i) With N Desg Dt(i) N Desl Mt(i) With N Dsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand for IgM desorption from bare silica is 0.004 ± 0.0025 min -1 and 0.00035 ± 0.00007 min -1 for monomers and dimers respectively. These values are well within the wide range of desorption rate constants (≈10 -4 min -1 to ≈1 min -1 ) found in the literature [120,[144][145][146]. Clearly, there are two important inferences: the monomer desorbs faster than the dimer for both surfaces, and the propensity for both the monomers and dimers of IgM to stay adsorbed on the gelatin-passivated surface is lower.…”
Section: N Desg Mt(i) With N Desg Dt(i) N Desl Mt(i) With N Dsupporting
confidence: 86%
“…The desorption rate constants are listed in Table 4.1. Using X-ray photoelectron spectroscopy, Ball et al [120] found desorption rate constant for IgG to be ≈ 10 -5 sec -1 , consistent with above results.…”
Section: Desorption Rate Constantssupporting
confidence: 80%
“…(Ball et al, 1996;Höök et al, 2002a;Huang et al, 2003;Imamura et al, 2008;Jones et al, 2000;Walivaara et al, 1994;Yang et al, 2003) These kind of biomaterial applications made of titanium are satisfactory products, because of their ability to adsorb certain proteins. After implantation, within a few seconds, the biomaterial surface becomes coated with a film of adsorbed proteins mediating the interaction between the implant and the body environment.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are widely used as implants. Titanium belongs to a specific group of materials, which are very stable and have high corrosion resistance and tissue tolerance [1][2][3][4]. This fact is mainly due to the creation of a protective layer formed on air and liquids on surfaces of titanium.…”
Section: Introductionmentioning
confidence: 99%